2016
DOI: 10.1177/0960327115621363
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidative stress in tri-ortho–cresyl phosphate-induced liver injury in male mice

Abstract: Tri- ortho–cresyl phosphate (TOCP) has been widely used as plasticizers, plastic softeners, and flame retardants in industry and reported to have delayed neurotoxicity and reproductive toxicology in animals. However, it remains to be elusive whether TOCP induces liver injury. In this study, male mice were orally administered different concentrations of TOCP (100, 200, or 400 mg/kg/day) for 28 days. Histological examination showed that TOCP led to serious hepatocellular injury. In addition, administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Recently, research on the TOCP toxicity in females reproductive tract lesions including an increase in the number of absorbed embryos and a reduction in the number of offspring vitality is mounting . However, whether it is associated with alteration of placental development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research on the TOCP toxicity in females reproductive tract lesions including an increase in the number of absorbed embryos and a reduction in the number of offspring vitality is mounting . However, whether it is associated with alteration of placental development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of people have suffered delayed neuropathy caused by TOCP‐contaminated food or beverages in the United States, India, Morocco, and other countries . Apart from the neurotoxicity, immunotoxicity, and liver toxicity, TOCP can also cause severe damage to mouse male reproductive system irreversibly, in which TOCP exposure decreases the sperm density in the epididymis and inhibits viability of spermatogonial stem cells and mouse Leydig TM3 cells . TOCP is also shown to cause ovarian failure .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is shown to be induced by many chemicals and plays an important role in reproductive toxicity . It has been reported that oxidative stress is involved in TOCP‐induced liver damage and autophagy of mouse Leydig TM3 cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al () found that Tris(2‐chloroethyl) phosphate and triphenyl phosphate induced oxidative stress in male mice liver and affected the expressions of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPX). Tri‐ortho‐cresyl phosphate exposure caused malondialdehyde accumulation as well as antioxidative enzymes SOD and GPX reduction in male mice liver (Xu et al ). Triphenyl phosphate and Tris(1,3‐dichloroisopropyl) phosphate induced oxidative stress in murine dendritic cells and increased antioxidant enzyme HO‐1 expression significantly (Canbaz et al ).…”
Section: Introductionmentioning
confidence: 99%